Sophie Levitt: capstone - Levitt, Sophie, artist (Colorado State University. Libraries, 2023)
The artist's statement: At the start of each studio session, I cultivate a positive atmosphere by organizing my workspace, ensuring materials are within reach, decluttering to prevent distraction, replenishing my energy with a snack, and activating my music speaker. Creating this organized and positive environment opens the door to a free-flowing and unconstrained thought process. Within this constructive environment, my material choices are guided by positivity and structure. I gravitate towards vibrant colors, shiny materials, and small objects, embracing whatever captures my attention. Given the diverse range of my small materials, I keep tweezers, a heat gun, various glues, and pliers close at hand. This marks the initiation of my creative journey. I delve into extensive experimentation with various materials and mediums, assessing how they complement each other. I rejuvenate this process through iterative cycles until a small object that captures my intrigue emerges. Before I embark on the creative cycle again, I set aside these pieces for potential future alterations. Creating many small objects through repeated iterations keeps my mind intrigued, curious, and stimulated. This immersive creative process transports me to an altered state where the constraints of time, external pressures, and boundaries cease to exist. I value the freedom, lack of constraints, and playfulness embedded in my creative process. Within this realm, I delve into a personal expedition through my psyche, involving exploration, critique, and self-reconstruction. This process empowers me to create art that functions as a tool for self-exploration, self-presentation, and self-therapy.
Beyond the surface
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture